2020
DOI: 10.7717/peerj.8515
|View full text |Cite
|
Sign up to set email alerts
|

Mutantdlx3bdisturbs normal tooth mineralization and bone formation in zebrafish

Abstract: Background Tricho-dento-osseous (TDO) syndrome is an autosomal dominant disorder characterized by anomalies in hair, teeth and bone (OMIM190320). Various mutations of Distal-Less 3 (DLX3) gene are found to be responsible for human TDO. The aim of this study was to investigate effects of DLX3 on tooth and bone development using a zebrafish model. Methods The dlx3b mutant zebrafish lines were established using the gene targeting tool transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In terms of the mineralization areas of the larval head skeleton, the 5.2-mM anisodaminetreated embryos showed a significant reduction compared with the control group (p < 0.01), whereas the 1.3-and 2.6-mM groups showed no difference (p > 0.05) (Figure 2C). Based on the previous reports (Pang et al, 2020;Xiong et al, 2017), these skeletal developmental abnormalities were associated with the observed curvature of the spine.…”
Section: Anisodamine Exposure To Zebrafish Embryos Caused Morphologic...mentioning
confidence: 64%
“…In terms of the mineralization areas of the larval head skeleton, the 5.2-mM anisodaminetreated embryos showed a significant reduction compared with the control group (p < 0.01), whereas the 1.3-and 2.6-mM groups showed no difference (p > 0.05) (Figure 2C). Based on the previous reports (Pang et al, 2020;Xiong et al, 2017), these skeletal developmental abnormalities were associated with the observed curvature of the spine.…”
Section: Anisodamine Exposure To Zebrafish Embryos Caused Morphologic...mentioning
confidence: 64%
“…The GO term “embryonic viscerocranium morphogenesis”, which encompasses a set of genes involved in the generation and organization of the facial skeleton, also included ASE genes directly implicated in tooth and jaw formation (Table S8). For instance, Dlx3b and Dlx1a , genes encoding members of the Dlx family of homeodomain transcription factors [35], are involved in tooth and jaw patterning in mammals and fish [36,37]. Thus, biased directionality of this process category may reflect selection for morphological changes to the freshwater fish in the facial region related to feeding morphology.…”
Section: Resultsmentioning
confidence: 99%
“…The following priors were selected to describe groups: θ(𝒩)∼Beta (2000,2000) θ(ℳ)∼ ½Beta(80,36)+ ½Beta (36,80) θ(𝒮)∼ ½Beta(80,7)+½Beta (7,80) Densities of the prior distributions for the proportion of allelic counts are found ins Figure S9. Parameters for Beta distributions were chosen to clearly separate the three groups from each other to allow the classification of tissues to a particular group, following Pirinen et al [23].…”
Section: Assessing Heterogeneity In Allele-specific Expression Across...mentioning
confidence: 99%
“…Subsequently, the SDL expands to form a replacement tooth germ. Naïve SDL in zebrafish expresses nine genes ( bmpr1aa , bmp6 , cd34 , gli1 , igfbp5a , lgr4 , lgr6 , nfatc1 , and pitx2 ), and active Wnt signaling and Lef1 are expressed during the early morphogenesis of the teeth (Pang et al, 2020). Rspo3 is a key regulator of Wnt signaling and it functions in the maintenance of teeth rather than tooth development, either by regulating tooth integrity or tooth regeneration in zebrafish.…”
Section: Craniomaxillofacial Developmental Disorders Of Zebrafishmentioning
confidence: 99%
“…dlx3b . An abnormal morphology of teeth with a reduction in mineral content was visible in dlx3b −/− zebrafish, suggesting that dlx3b is critical for enamel mineralization in zebrafish (Pang et al, 2020).…”
Section: Craniomaxillofacial Developmental Disorders Of Zebrafishmentioning
confidence: 99%